A Chemical Probe for the ATAD2 Bromodomain. Issue 38 (17th August 2016) - Bamborough, Paul; Chung, Chun‐wa; Demont, Emmanuel H.; Furze, Rebecca C.; Bannister, Andrew J.; Che, Ka Hing; Diallo, Hawa; Douault, Clement; Grandi, Paola; Kouzarides, Tony; Michon, Anne‐Marie; Mitchell, Darren J.; et al.
Abstract: ATAD2 is a cancer‐associated protein whose bromodomain has been described as among the least druggable of that target class. Starting from a potent lead, permeability and selectivity were improved through a dual approach: 1) using CF2 as a sulfone bio‐isostere to exploit the unique properties of fluorine, and 2) using 1, 3‐interactions to control the conformation of a piperidine ring. This resulted in the first reported low‐nanomolar, selective and cell permeable chemical probe for ATAD2. Abstract : ANCCA away : ATAD2 or ANCCA is a cancer‐associated bromodomain‐containing protein. Starting from a potent lead, permeability and selectivity over BET bromodomains were improved by 1) using CF2 as a sulfone bio‐isostere to exploit the unique properties of fluorine, and 2) using 1, 3‐interactions to control the conformation of a piperidine ring. GSK8814 is the first low‐nanomolar, selective and cell‐permeable chemical probe for ATAD2.